Waste from the electronics industry and environmental pollution - Guamán-Segarra, Julio Cesar; Maza-Vivanco, Dolores Vanessa; Caballero-Giler, Beatriz Irene; Guerrero-Alcivar, Maria Shirlendy; Caicedo Arevalo, Olinda Elizabeth (The International tax journal, 2024)
One of the current problems that hits technological development the hardest is environmental pollution caused by waste. The development of electronics is advancing every day and with this, waste problems become a problem that affects health and the environment. Therefore, it is necessary to draw up strategies to mitigate them. The objective of the research is to know the main pollutants and propose solutions for their mitigation. The methodology used was the bibliographic search, the inductive and deductive method, and the proposal of some strategies to mitigate them mitigate the polluting effects of waste electrical industry where one of the aspects considered most relevant is education and awareness of the people who produce, use and manage these pollutants.